Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Kota Samarinda - Jeremia Hasiholan Napitupulu; Noor Ellyawati; Ratna Fitri Astuti (Jurnal Pendidikan Ekonomi (JUPE), 2021)
The role of financial literacy and financial attitude is important in producing wise behavior in student financial management. This research aims to determine how the influence of financial literacy and financial attitudes on student financial management behavior. Data collection was carried out by distributing questionnaires to 110 Samarinda’s students to find out responses to the condition of financial literacy, financial attitudes and student financial management behavior. Based on the analysis results show that partially and simultaneously, the higher the financial literacy and financial attitude, the higher the student's financial management behavior. Students who have good behavior show that students are able to apply their knowledge and attitudes in their financial management behavior. Optimization of financial literacy and attitudes is needed, so that student's behavior in managing finances is getting better in order to face increasingly complex financial problems in the future